CORE VALUES AND EMPLOYER BRANDING ARE MORAL TO IMPROVE ISLAMIC SERVICES IN THE JANUR KUNING HOME INDUSTRY IN REJING VILLAGE, PROBOLINGGO REGENCY - Qurrota A'yun (Universitas Nurul Jadid, 2023)
This research aims to analyze the relationship between the application of core values and employer branding strategies in improving Islamic services in the Janur Kuning home industry in Rejing Village, Probolinggo Regency. The Janur Kuning home industry has become an integral part of the culture and economy of the local community, with a significant contribution to local economic development. This research method uses a qualitative approach through in-depth interviews and participatory observation of business owners and employees of the Janur Kuning home industry. This research also involves analysis of documentation related to the core values implemented in the business and employer branding strategies that have been carried out. The research results show that the application of core values, such as honesty, courage, friendliness and justice, has become a strong basis for the work culture in the Janur Kuning home industry. The application of these values does not only affect the internal relationship between business owners and employees. However, it also has an impact on interactions with customers and society in general. Apart from that, the employer branding strategy which focuses on developing the company's image as an Islamic and value-oriented workplace has helped improve the Islamic services provided by the Janur Kuning home industry. Steps such as training employees in Islamic values. Implementation of fair and transparent work patterns, as well as involvement in Islamic social activities which have improved the company's reputation in the eyes of customers and the community. In conclusion, the application of core values and employer branding strategies that focus on Islam has helped the Janur Kuning home industry to improve their Islamic services. The implication of this research is the importance of strengthening a company culture based on Islamic values, as well as developing an Islamic company image in an effort to increase customer trust and loyalty.